Ответ:
........................
1. -1
2. 0
3. 10
4. 73
Пошаговое объяснение:
1) (-7)+(-8)+(+7)+(+7) = (-7 + 7) + (-8 + 7) = 0 - 1 = -1
2) (-1)+(+2)+(+1)+(-2) = (-1 + 1) + (2 - 2) = 0 + 0 = 0
3) (-8)+(-6)+(-4)+(+28) = (-8 - 6 - 4) + 28 = -18 + 28 = 10
4) (+19)-(-20)-(-39)+(-5) = (19 - 5) - (-20 - 39) = 14 - (-59) = 14 + 59 = 73
Copyright © 2025 SCHOLAR.TIPS - All rights reserved.
Answers & Comments
Ответ:
........................
Ответ:
1. -1
2. 0
3. 10
4. 73
Пошаговое объяснение:
1) (-7)+(-8)+(+7)+(+7) = (-7 + 7) + (-8 + 7) = 0 - 1 = -1
2) (-1)+(+2)+(+1)+(-2) = (-1 + 1) + (2 - 2) = 0 + 0 = 0
3) (-8)+(-6)+(-4)+(+28) = (-8 - 6 - 4) + 28 = -18 + 28 = 10
4) (+19)-(-20)-(-39)+(-5) = (19 - 5) - (-20 - 39) = 14 - (-59) = 14 + 59 = 73